Petrochemistry of Ultramafic Rock in Baula - Pomalaa Ophiolite Complex, Southeast Sulawesi, Indonesia - Cendrajaya, Rio Irhan Mais; Juarsan, Laode Ihksan; Masri; Rubaiyn, Al; Syahrul; Neni; Ramadani, Suci; Hasria (UIR PRESS, 2024)
Baula and Pomalaa Ophiolitic Complexes are part of East Sulawesi Ophiolite (ESO). The ultramafic rocks in the Baula and Pomalaa Ophiolite Complex mainly is peridotite and consist of harzburgite, lherzolite and olivine websterite, mostly serpentinized. Chemical and petrological research has focused on minerals, such as olivine, pyroxene, and spinel. This study examines the tectonic setting and temperature of ultramafic rock formation. Twelve ultramafic rock samples were examined using geothermometers made of pyroxene, petrographic examination, and coexisting olivine and spinel analyses. SEM and petrographic analysis of pyroxene lamellae and mylonite-ultramylonite structures allowed for the measurement of the geothermometer of ultramafic rocks. Using SEM-EDS, the coexistence of olivine and spinel was analyzed to determine the type of ultramafic tectonic setting. In the coexistence of olivine and spinel, olivine and spinel oxide compounds as tectonic setting markers in the form of Fo and Cr# values. Ultramafic rocks have different temperature levels, based on pyroxene thermometer, and the first one starts at a high temperature of 1000-1200ºC. It is characterized by thin, elongated augite lamellae. Instead, large lamellae characterize augite at medium temperatures (800–1000ºC). Irregular, anhedral, and broader forms of enstatite lamellae are typical of low temperatures (500–800ºC). Different generations of exsolution lamellae indicate that magma cooling was gradual. The distribution of #Fo ranged from 0.87 to 0.92, and Cr# values ranged from 0.13-0.19. According to coexisting olivine and spinel analysis. On the Olivine-Spinel Mantle Array (OSMA), the Fo and Cr# plot indicates that the peridotites tectonic setting was from the ocean floor and the magmatism was from MORB (Mid Oceanic Ridge Basalt). The Al2O3 vs. TiO2 pattern in spinel lherzolite also similar with Ampana and Kabaena peridotites magmatism.